Why Isn't the Doha Development Agenda More Poverty Friendly? - Hertel, Thomas W. (2012)
Critics of the Doha Development Agenda rightly point to the lack of aggressive reform in wealthy countries for its role in dampening developing country gains. The authors find that the absence of tariff cuts on staple food products in developing countries also critically limits poverty reduction in those countries. Based on their analysis of the impacts of multilateral trade policy reforms in a sample of 15 developing countries, they find there is some evidence of poverty increases amongst the poor who work in agriculture when they lose protection for their earnings. However, these effects are minimized when agricultural tariffs are cut in all developing countries, and when the impact of lower food prices on low income consumers is taken into account in their 15 country sample.